2022
DOI: 10.1021/acs.accounts.2c00184
|View full text |Cite
|
Sign up to set email alerts
|

C(sp3)-Arylation by Conformationally Accelerated Intramolecular Nucleophilic Aromatic Substitution (SNAr)

Abstract: Conspectus The asymmetric synthesis of heavily substituted benzylic stereogenic centers, prevalent in natural products, therapeutics, agrochemicals, and catalysts, is an ongoing challenge. In this Account, we outline our contribution to this endeavor, describing our discovery of a series of new reactions that not only have synthetic applicability but also present significant mechanistic intrigue. The story originated from our longstanding interest in the stereochemistry and reactivity of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…15 The T-S rearrangement 11 can also produce arylated products via a 2-electron pathway and is similar to S N Ar reactions. While Truce-Smiles rearrangement reactions generally require electron-withdrawing groups, the original work by Truce 16 and recent studies by Clayden 17,18 and others 19,20 have demonstrated that electron-withdrawing groups are not always needed.…”
Section: Introductionmentioning
confidence: 99%
“…15 The T-S rearrangement 11 can also produce arylated products via a 2-electron pathway and is similar to S N Ar reactions. While Truce-Smiles rearrangement reactions generally require electron-withdrawing groups, the original work by Truce 16 and recent studies by Clayden 17,18 and others 19,20 have demonstrated that electron-withdrawing groups are not always needed.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Shibata et al demonstrated an asymmetric synthesis of CF 3 -substituted nine-membered heterocycles by Pd-catalyzed decarboxylative ring expansion strategy, [9] and the enantioselec-tive construction of medium ring bridged biaryls is noteworthy. [10] Ring expansion is a particularly appealing approach to the synthesis of medium rings, [11] and we previously reported the racemic ring expansion, by a conformationally accelerated intramolecular S N Ar reaction, [12] of benzo-fused heterocycles (ring size n) to provide cyclic ureas with ring size n + 3 (Scheme 1b). [13] In this paper, we now show that a related ring expansion can be rendered asymmetric by the employment of a chiral lithium amide base, and furthermore that the acid-promoted 'azatropic shift' [14] of the product ureas, which induces re-contraction back to a benzo-fused nitrogen heterocycle of ring size n + 1, is remarkably stereochemically retentive.…”
mentioning
confidence: 99%
“…Optimal conditions for bases 3 and 4 (entry 7) and found to be comparable, with slightly higher er from 3. We assume that DMPU [18] induces the formation of a solvent-separated ion pair that engages rapidly in the unactivated S N Ar reaction [12,19] required for enantioselective ring expansion.…”
mentioning
confidence: 99%
“…Only the original work (Scheme 1b) and more recent works by Clayden have proven effective. [3,5] On the other hand, the diversity of the Truce-Smiles rearrangement can be expanded by altering the migrating aromatic rings or the leaving linker groups. [3] To date, the linking atom (A) including carbon, [6] nitrogen, [7] phosphorous, [8] oxygen, [9] or most commonly, sulphur in sulfones, [10] have been documented to be suitable for these AÀ C aryl migrations.…”
mentioning
confidence: 99%